Application of UV-C technology in extending the shelf life of fresh blueberries : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology at Massey University, Albany, New Zealand. EMBARGOED until 1st August 2027 - Akram, Sidra (Massey University, 2024)
Fresh blueberry fruit is highly perishable and susceptible to spoilage by bacteria and fungi resulting in a short postharvest shelf life. Ultraviolet light treatment (UV-C) in the range is considered an emerging novel food processing technique that can be used to improve fruit quality and thus prolong the shelf life. The study investigated the impact of UV-C light treatment on untreated fresh blueberry farthing variety. The study was conducted in three phases to analyse and optimize the most suitable dosages to be applied to the sample and determine its effects on the fruit sample during the 14 days of storage at 4°C. The fruit sample was collected from a local blueberry farm and transported to the Massey University, Auckland campus. In phase one, the fresh blueberry fruit was treated with different dosages of UV-C (50, 100, 200, 300, 400, 600 mJ/cm²) using a JouleSafe disinfection system. Focus group sensory evaluation was used to analyse the consumer acceptance of the UV-C treated fruit alongside the microbial enumeration to narrow down the range of dosages.--Shortened abstract.
Figures are reproduced with permission. Embargoed until 1st August 2027.
Keywords: 300604 Food packaging, preservation and processing; 300806 Post harvest horticultural technologies (incl. transportation and storage)